Contribution of Different Mechanisms to Ciprofloxacin Resistance in Salmonella spp. - Chang, Man-Xia; Zhang, Jin-Fei; Sun, Yin-Huan; Li, Rong-Sheng; Lin, Xiao-Ling; Yang, Ling; Webber, Mark A.; Jiang, Hong-Xia (Frontiers in Microbiology, 2021)
Development of fluoroquinolone resistance can involve several mechanisms that include chromosomal mutations in genes (gyrAB and parCE) encoding the target bacterial topoisomerase enzymes, increased expression of the AcrAB-TolC efflux system, and acquisition of transmissible quinolone-resistance genes. In this study, 176 Salmonella isolates from animals with a broad range of ciprofloxacin MICs were collected to analyze the contribution of these different mechanisms to different phenotypes. All isolates were classified according to their ciprofloxacin susceptibility pattern into five groups as follows: highly resistant (HR), resistant (R), intermediate (I), reduced susceptibility (RS), and susceptible (S). We found that the ParC T57S substitution was common in strains exhibiting lowest MICs of ciprofloxacin while increased MICs depended on the type of GyrA mutation. The ParC T57S substitution appeared to incur little cost to bacterial fitness on its own. The presence of PMQR genes represented an route for resistance development in the absence of target-site mutations. Switching of the plasmid-mediated quinolone resistance (PMQR) gene location from a plasmid to the chromosome was observed and resulted in decreased ciprofloxacin susceptibility; this also correlated with increased fitness and a stable resistance phenotype. The overexpression of AcrAB-TolC played an important role in isolates with small decreases in susceptibility and expression was upregulated by MarA more often than by RamA. This study increases our understanding of the relative importance of several resistance mechanisms in the development of fluoroquinolone resistance in Salmonella from the food chain.